Ten Year Insulin-Independence in Select Islet Transplant Recipients Receiving CNI-Sparing Immunosuppression with Either Costimulation Blockade or Anti-LFA1. (July 2018) - Gardner, James M; Posselt, Andrew M; Wisel, Steven; Mashirani, Umesh; Szot, Greg; Nguyen, Vinh; Johnson, Kristina; McElroy, Joan; Tang, Qizhi; Stock, Peter G
Abstract : Introduction: Long-term islet graft function remains challenging in part due to chronic Calcineurin inhibitor (CNI) toxicity. Here we present 10-year outcomes from a cohort of patients receiving CNI-sparing immunosuppression (IS) with either the anti-leukocyte functional antigen-1 (LFA-1) antibody Efalizumab or Belatacept. Methods: Patients underwent portal infusion of islets and induction with thymoglobulin and prednisone withdrawal. Patients remained on Efalizumab from transplant until drug discontinuation on May 1, 2009 (average 570 days), at which point they were transitioned to maintenance therapy with sirolimus and mycophenolate (MMF) or MMF monotherapy. Belatacept patients remained on maintenance IS including monthly belatacept, sirolimus, and MMF. Blood was monitored pre- and post-transplant for immune phenotyping, including percentage of CD4+, CD8+, and regulatory T (Treg) cells. Recipient alloreactivity was evaluated by mixed lymphocyte reactions (MLR) in vitro against donor-specific and third-party stimulated B cells (sBc) for proliferation and cytokine production. Results: At 10 years post-transplant, insulin-independence was 40% (2/5 patients) in both the Efalizumab and Belatacept arms (Fig. 1). In the Efalizumab arm, one patient achieved operational tolerance (EFA-4), maintaining insulin-independence following complete IS withdrawal, while another patient (EFA-2) remained on single-drug IS with MMF. Two patients returning to insulin dependence (EFA-3, EFA-5) received pancreas-after-islet (PAI) transplants. For the belatacept arm, both patients maintaining insulin independence remained on combination IS with belatacept, MMF, and sirolimus. Patients who received Efalizumab showed a profound enrichment of peripheral Tregs relative to patients receiving Belatacept (p=0.0076). Notably, the patient who remains insulin-independent 5.4 years after withdrawal of all IS (EFA-4) had the highest levels of Treg-predominance, reaching 67% of all CD4+ T cells in circulation at one month post-transplant. Further investigation of Efalizumab patients by proliferation and interferon gamma production after MLR revealed that EFA-2 and EFA-4 had an extended period of non-reactivity to donor and third-party antigen while on Efalizumab (Fig. 2). Despite regaining in vitro reactivity to both donor and third-party antigen after discontinuation of Efalizumab, EFA-4 remained operationally tolerant and insulin-independent off all IS. Conclusions: In 10-year follow up of islet transplant recipients on Efalizumab-based versus Belatacept-based IS (n=5 per group), one patient was able to achieve operational tolerance, with three others maintaining insulin independence. The mechanisms underlying these multiple pathways to insulin independence remain unclear, although selective enrichment of Tregs, sustained early donor non-reactivity while on Efalizumab, and CNI avoidance may play a role in the success of these regimens. Figure. No caption available. Figure. No caption available.